On the possibility of an ever-increasing wealth concentration: Pasinetti, dual, and anti-dual equilibria in a Post-Keynesian framework - Stefan Ederer; Miriam Rehm (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
This paper develops a stock-flow consistent Post-Keynesian model in the Kalecki-Steindl tradition with endogenous wealth accumulation and distribution, which captures the key aspects of the Cambridge debate on (anti-)dual and Pasinetti equilibria. We find that a stable interior solution - that is, a Pasinetti equilibrium - is the most likely outcome, while the corner solutions of dual and anti-dual equilibria - both the euthanasia and the triumph of the rentier - are special cases of a standard Bhaduri-Marglin model. Endogenizing the profit share yields a two-dimensional dynamic system of the wealth concentration and the profit share, which is stable for a wide range of parameter values, as long as the concentration of wealth is not unrealistically low. An interior Pasinetti equilibrium thus remains the most likely outcome. However, for certain parameter combinations, the system may move onto an explosive trajectory with an ever-rising concentration of wealth and income in the hands of capitalists. Numerically illustrating the results of the analytical model shows that endogenizing the profit share leads to a more unequal wealth distribution, and a negative feedback effect between high wealth inequality, a high profit share, and growth.
Keywords: B22; D31; D33; E12; E21; E64; 330; wealth distribution; Post-Keynesian model; aggregate demand; Pasinetti; profit rate